2017
DOI: 10.4184/asj.2017.11.6.880
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Complications of Postoperative Transfusion for Cervical Fusion Procedures in Spine Surgery: An Analysis of 11,588 Patients from the American College of Surgeons National Surgical Quality Improvement Program Database

Abstract: Study DesignRetrospective cohort study.PurposeThe purpose of this study was to assess the rate of blood transfusion after cervical fusion surgery, and its effect on complication rates.Overview of LiteratureCervical spine fusions have gained interest in the literature since these procedures are now ever more frequently being performed in an outpatient setting with few complications.MethodsThe American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) database was used to identify pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 20 publications
(29 reference statements)
0
26
0
Order By: Relevance
“…Five studies [ 11 , 25 , 27 , 29 , 33 ] including 72,493 patients assessed the relationship between a blood transfusion and the incidence of VTE. As 1 study [ 33 ] included the patients undergoing lumbar and thoracic fusion surgery, another study [ 29 ] included patients undergoing cervical fusion surgery, subgroup analysis was performed according to the surgery site. The pooled data revealed that a blood transfusion remarkably increased the incidence of VTE (OR 4.050, 95% CI 2.825–5.805; P < .001).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies [ 11 , 25 , 27 , 29 , 33 ] including 72,493 patients assessed the relationship between a blood transfusion and the incidence of VTE. As 1 study [ 33 ] included the patients undergoing lumbar and thoracic fusion surgery, another study [ 29 ] included patients undergoing cervical fusion surgery, subgroup analysis was performed according to the surgery site. The pooled data revealed that a blood transfusion remarkably increased the incidence of VTE (OR 4.050, 95% CI 2.825–5.805; P < .001).…”
Section: Resultsmentioning
confidence: 99%
“…These results were in line with previous studies. [ 11 , 27 , 29 , 33 ] Three studies [ 11 , 27 , 33 ] observed a relationship between postoperative transfusion and the incidence of VTE in patients who had undergone lumbar spinal surgery. Aoude et al [ 33 ] retrospectively analyzed the American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) database to identify patients who underwent lumbar or thoracic fusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, numerous other investigators have further carried the clinical inquiry and geared the prediction model development toward other clinical outcomes of interest. [89][90][91][92][93][94][95] Additionally, other teams have extended their investigations to other patient populations more representative of their local settings. 22,[96][97][98][99][100] With the rise of contemporary value-based bundled health care models, interest in cost improvement strategies that do not compromise the quality of care have also led to the development of predictive models to estimate prolonged hospital stay and adverse discharge destination for elective spine surgery.…”
Section: Prediction Modelingmentioning
confidence: 99%
“…132 Today, the high-quality data have appealed to numerous investigators and attracted a wide range of spine-related studies primarily focused on surgical outcomes, adverse events, as well as predictive modeling. [88][89][90][91][92][93][94][95]101,109,[134][135][136] A recent systematic review conducted by Marjoua et al 137 found 40 spinespecific peer-reviewed publications based on the NSQIP data between 2010 and 2015. While the magnitude and quality of data have proven the compelling research merit of NSQIP, the success of the program in improving surgical care owes to the fact that it stands as a national standard to which individual institution can compare their performance.…”
Section: Quality Improvement Initiativementioning
confidence: 99%